Perceptions and knowledge toward cosmetic procedures: A cross-sectional survey - Vildan Manav; Dilara İlhan; Elif Bal Avcı; Asude Kara Polat; Duygu Erdil; Soysal Baş; Ayşe Esra Koku Aksu (Galenos Publishing House, 2022)
Background and Design: Cosmetic procedures have been increasing recently, and public knowledge on this issue is made available through the internet, television, or social media. However, with the increasing tendency for these procedures, the risk of complications also increases because of practitioners who do not have expertise in this field. This study aimed to determine the perceptions and knowledge toward cosmetic procedures and its complications. Materials and Methods: A total of 324 patients aged 18 years and over presented to the cosmetology outpatient clinic. Results: The majority of the participants stated that dermatologists and/or plastic surgeons are the most qualified to perform cosmetic procedures (77.2%). Particularly, female participants and the high-income group answered that they will choose dermatologists and plastic surgeons for performing cosmetic procedures (p=0.028 and p=0.010, respectively). Conclusion: While most of the participants perceived that these procedures are performed by dermatologists or plastic surgeons, cosmetic procedures are performed in the skin care center by non-healthcare providers because of socio-economic reasons. However, if complications occur, patients first sought dermatologists for treatment. Therefore, society should be more conscious of this issue when planning to undergo cosmetic procedures by experts and to prevent complications.